Cost-effectiveness of mechanical thrombectomy for acute ischemic stroke in Brazil: Results from the RESILIENT trial. Issue 8 (October 2022) - de Souza, Ana Claudia; Martins, Sheila O; Polanczyk, Carisi Anne; Araújo, Denizar Vianna; Etges, Ana Paula BS; Zanotto, Bruna Stella; Neyeloff, Jeruza Lavanholi; Carbonera, Leonardo Augusto; Chaves, Márcia Lorena Fagundes; de Carvalho, João José Freitas; Rebello, Letícia Costa; Abud, Daniel Giansante; et al.
Background: The RESILIENT trial demonstrated the clinical benefit of mechanical thrombectomy in patients presenting acute ischemic stroke secondary to anterior circulation large vessel occlusion in Brazil. Aims: This economic evaluation aims to assess the cost-utility of mechanical thrombectomy in the RESILIENT trial from a public healthcare perspective. Methods: A cost-utility analysis was applied to compare mechanical thrombectomy plus standard medical care (n = 78) vs. standard medical care alone (n = 73), from a subset sample of the RESILIENT trial (151 of 221 patients). Real-world direct costs were considered, and utilities were imputed according to the Utility-Weighted modified Rankin Score. A Markov model was structured, and probabilistic and deterministic sensitivity analyses were performed to evaluate the robustness of results. Results: The incremental costs and quality-adjusted life years gained with mechanical thrombectomy plus standard medical care were estimated at Int 7440 and 1.04, respectively, compared to standard medical care alone, yielding an incremental cost-effectiveness ratio of Int 7153 per quality-adjusted life year. The deterministic sensitivity analysis demonstrated that mRS-6 costs of the first year most affected the incremental cost-effectiveness ratio. After 1000 simulations, most of results were below the cost-effective threshold. Conclusions: The intervention's clear long-term benefits offset the initially higher costs of mechanical thrombectomy in the Brazilian public healthcare system. Such therapy is likely to be cost-effective and these results were crucial to incorporate mechanical thrombectomy in the Brazilian public stroke centers.